Design Smart Trash Based On the Inductive Proximity Sensor - Wulandari, Rindi; Ariwibowo, M. Riyad; Taryo, Taryo; Ananda, Galieh (International Journal of Multidisciplinary Approach Research and Science, 2024)
Smart waste management, including a waste sorting system based on type, strongly supports the "Intelligent waste management and categorization system" program to support the development of modern cities. Therefore, this research is related to the design of smart waste based on an inductive distance sensor that uses Arduino Uno as a microcontroller. The method used in this research is research and development which consists of mechanical design and control system programming. The results obtained from this research are an intelligent waste design based on an inductive distance sensor that uses Arduino Uno as a microcontroller and uses a conveyor system as a waste transporter. The test results on the ultrasonic sensor were that several objects could be detected at a distance of 15 cm and the conveyor stopped for 0.5 seconds. The test results on the proximity sensor are that the object is read by the proximity sensor when the object is 2 cm from the sensor, and if the object is metal waste then the servo motor moves 30 degrees to the right, if it is non-metallic waste then the servo motor moves 30 degrees to the left